Régimen laboral y compromiso organizacional de los trabajadores del Instituto Nacional Penitenciario Iquitos 2024 - Vilca Nuñez, Telmo Nolasco (2025)
The objective of this study was to determine the relationship between the work regime and organizational commitment of the workers of the National Penitentiary Institute Iquitos 2024. The research was of an applied type, with a descriptive-correlational level and using a non-experimental cross-sectional design. The study population included 144 workers from the National Penitentiary Institute of Iquitos. It was concluded that the work regime is considered adequate with (34%) this perception is due to the fact that the workers clearly understand the procedure to change the work regime within the public sector. They are also satisfied with the rules that regulate the payment of overtime in their work regime, as well as with the types of licenses and permits available. Regarding the level of organizational commitment, it is rated as high (34%). due to the willingness of the workers to work and grow in the institution, which generates satisfaction for them. They are also satisfied with the rules and positively value what the institution has given them, demonstrating their willingness to remain and contribute to its development. Finally, the remarkable correlation between work arrangements (coefficient of 0.832) and benefits (coefficient of 0.869) with organizational commitment indicates that these dimensions are essential to increase employee engagement. On the other hand, the moderate relationship between knowledge and organizational commitment (coefficient of 0.611) underlines the importance of promoting training and professional development.